2002
DOI: 10.1177/0022022102033002001
|View full text |Cite
|
Sign up to set email alerts
|

Parental Warmth, Control, and Involvement in Schooling

Abstract: This study explored the relationship between Baumrind’s parenting prototypes and the academic achievement, judged by grade point average (GPA), of Korean American adolescents. It also examined the relative contribution to youth’s academic achievement of perceived maternal and paternal warmth and control and involvement in schooling. Approximately 74% of the sample youth did not fit any of Baumrind’s types, raising questions about their usefulness for ethnic research. Analysis of the remaining 26% showed that y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(49 citation statements)
references
References 34 publications
3
42
0
4
Order By: Relevance
“…In contrast, there was no significant relationship between authoritarian parenting style and school achievement. The present finding is similar to the findings by Kim and Rohner (2002), Park andBauer (2002), andOlige (2008). Authoritarian parents tend to practice rigid and high level of monitoring.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, there was no significant relationship between authoritarian parenting style and school achievement. The present finding is similar to the findings by Kim and Rohner (2002), Park andBauer (2002), andOlige (2008). Authoritarian parents tend to practice rigid and high level of monitoring.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, Paulson and Sputa [63] reported that adolescents (and parents) perceived mothers to be more involved in schooling at home (e.g., helping with schoolwork) and at school (e.g., attending school events) than fathers, although youth did not perceive differences between mothers and fathers in academic socialization (e.g., expectations about academic achievement). Kim and Rohner [64] reported that father involvement, but not mother involvement, mediated the relationship between father warmth and academic achievement in a sample of Korean families.…”
Section: Differences Between Mother and Father Involvementmentioning
confidence: 99%
“…Other commonly used scales that measure the four parenting styles though two dimensions are the Warmth/Affection Scale (WAS; Rohner et al, 1978; Rohner, 2005) and the Parental Control Scale (PCS; Rohner, 1989; Rohner and Khaleque, 2003). These two scales have been used jointly to create the four parenting styles typology (Kim and Rohner, 2002). The WAS measures the extent to which adolescents perceive their parents as loving, responsive, and involved, whereas the PCS assesses the extent to which an adolescent perceives strict parental control in their parents’ behavior.…”
Section: Introductionmentioning
confidence: 99%